Evaluating Brain-in-Hand for adults with an acquired brain injury - Kettlewell, Jade (2019)
Over one million people live with the long-term consequences of acquired brain injury (ABI). Individuals with ABI may find it difficult to self-manage the effects of injury and it is important to provide them with the skills to live independently. Many smart technologies exist to aid rehabilitation, but there is limited technology available to support self-management. Brain-in-Hand (BiH) is a smartphone application that was specifically engineered to support the management of persistent emotional and behavioural problems, which are commonly seen following ABI. However, it has not been systematically evaluated in this population. The aim of this thesis was to understand the perspectives and experiences of people with ABI and healthcare professionals after using BiH.